Interpersonal Communication of Single Mother in Supporting The Continuity of Their Children’s Education During Adolescence in Yogyakarta - Andin, Alifta Putri Andhini; Aulia, Aly (Jogjakarta Communication Conference (JCC), 2025)
Single mothers' interpersonal communication plays a crucial role in supporting their children's education during adolescence in Yogyakarta. This research aims to analyze and understand the interpersonal communication strategies used by single mothers to ensure the continuity of their children's education. This study uses a descriptive method with a qualitative approach, involving in-depth interviews with single mothers and adolescents as respondents. The results show that supportive interpersonal communication, such as providing emotional support, active listening, and positive feedback, can increase adolescents' self-confidence and engagement in the educational process. In interpersonal communication, verbal aspects (words, advice) and emotional aspects (empathy, affection) are essential for building strong emotional bonds. However, time constraints and economic pressures often pose challenges to maintaining consistent communication. This study concludes that despite various barriers, effective interpersonal communication remains a key factor in supporting adolescents' educational success.